Soilborne diseases of vegetable crops. Issue 2 (24th May 2016) - Koike, Steven T.
Abstract : This article looks discusses four reasons why soilborne diseases are so challenging for vegetable producers and examines a case study of a soilborne disease—Pythium wilt in California. Earn 0.5 CEUs in Integrated Pest Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/767 .